Tinnitus Is Associated With Improved Cognitive Performance in Non-hispanic Elderly With Hearing Loss - Hamza, Yasmeen; Zeng, Fan-Gang (Frontiers in Neuroscience, 2021)
Because hearing loss is a high-risk factor for cognitive decline, tinnitus, a comorbid condition of hearing loss, is often presumed to impair cognition. The present cross-sectional study aimed to delineate the interaction of tinnitus and cognition in the elderly with and without hearing loss after adjusting for covariates in race, age, sex, education, pure tone average, hearing aids, and physical well-being. Participants included 643 adults (60-69 years old; 51.3% females) from the National Health and Nutrition Examination Survey (NHANES, 2011-2012), and 1716 (60-69 years old; 60.4% females) from the Hispanic Community Health Study (HCHS, 2008-2011). Multivariable linear and binary logistic regression was used to assess the association between tinnitus and cognition in the two sub-cohorts of normal hearing (NHANES, n= 508; HCHS, n= 1264) and hearing loss (NHANES, n= 135; HCHS, n= 453). Cognitive performance was measured as a composite z-score from four cognitive tests: The Consortium to Establish a Registry for Alzheimer’s Disease (CERAD)-word learning, CERAD-animal fluency, CERAD-word list recall, and the digit symbol substitution test (DSST) in NHANES, and a comparable Hispanic version of these four tests in HCHS. Multivariable linear regression revealed no association between tinnitus and cognition, except for the NHANES (non-Hispanic) participants with hearing loss, where the presence of tinnitus was associated with improved cognitive performance (Mean= 0.3; 95% CI, 0.1– 0.5; p, 0.018). Using the 25th percentile score of the control (i.e., normal hearing and no tinnitus) as a threshold for poor cognitive performance, the absence of tinnitus increased the risk for poor cognitive performance (OR=5.6, 95% CI, 1.9– 17.2; p, 0.002). Sensitivity analysis found a positive correlation between tinnitus duration and cognitive performance in the NHANES cohort (F (4,140), 2.6; p, 0.037). The present study finds no evidence for the assumption that tinnitus impairs cognitive performance in the elderly. On the contrary, tinnitus is associated with improved cognitive performance in the non-Hispanic elderly with hearing loss. The present result suggests that race be considered as an important and relevant factor in the experimental design of tinnitus research. Future longitudinal and imaging studies are needed to validate the present findings and understand their mechanisms.